Sociālpedagoģiskā darbība neattaisnotu kavējumu mazināšanā Pumpuru vidusskolas 8. un 9. klasēs - Ludāne, Ineta (Latvijas Universitāte, 2009)
Diplomdarbā risina aktuālu problēmu par 8. un 9.klašu skolēniem, kuri neattaisnotu iemeslu dēļ kavē skolu. Tika veikts pētījums 2007./08.māc.g. un 2008./09.māc.g. 8. – 9.klasēs, lai noskaidrotu, kādi ir galvenie skolas neapmeklēšanas iemesli. Pēc aptaujas rezultātiem var secināt, ka skolēniem nav motivācijas mācīties, un dažiem trūkst vecāku atbalsta. Autores izstrādātā programma dod iespēju skolotājiem, sociāliem pedagogiem, psihologiem turpināt darbu, lai samazinātu neattaisnotos kavējumus dažādās izglītības iestādēs Latvijā. Darbā ir uzdevumi un padomi kā novērst neattaisnotos kavējumus un palīdzēt skolēniem atgriezties mācību procesā. Atslēgas vārdi: audzināšana, atbalsta komanda, ģimene, motivācija, neattaisnotie kavējumi, sociālpedagoģiskā darbība.

The Diploma Paper deals with the topical problem concerning 8 and 9-grade pupils that are absent due to unjustified reasons. The case study was carried out in the grades 8 and 9, academic years 2007/2008 and 2008/2009 in order to find out the main reasons for unjustified absences at school. The results gathered proved that pupils do not have enough motivation to learn and in several cases there are a lack of family support. The programme developed by the author of the Paper gives an oppurtunity for teachers, social educators, psychologists to continue to work in order to reduce the number of unjustified absences in various educational institutions in Latvia. The Diploma Paper describes tasks and advice to reduce the number of unjustified absences as well as to help pupils to get back into the active learning process. Key words: unjustified absences, family, upbringing, motivation, support team, socio-pedagogical activities.
Socialpedagogical activities in decreasing the cases of no- attending the school and in preventing drop- outs in Grades 8 and 9 of Pumpuri
Keywords: Pedagoģija